Application of the unified protocol for the transdiagnostic treatment of comorbid emotional disorders in patients with ultra-high risk of developing psychosis: A randomized trial study protocol - Peláez, Trinidad; López-Carrillero, Raquel; Ferrer-Quintero, Marta; Ochoa, Susana; Osma, Jorge (Frontiers in Psychology, 2022)
1 Background: Cognitive Behavioural Therapy is delivered in most of the early intervention services for psychosis in different countries around the world. This approach has been demonstrated to be effective in decreasing or at least delaying the onset of psychosis. However, none of them directly affect the comorbidity of these types of patients that is often the main cause of distress and dysfunctionality. The Unified Protocol for the Transdiagnostic Treatment of Emotional Disorders (UP) is a psychological intervention that combines cognitive-behavioral and third-generation techniques that address emotional dysregulation as an underlying mechanism that these disorders have in common. The application of this intervention could improve the comorbid emotional symptoms of these patients. 2 Methods: The study is a randomised controlled trial in which one group receives immediate UP plus standard intervention and the other is placed on a waiting list to receive UP 7 months later, in addition to standard care in one of our early psychosis programs. The sample will be 42 patients with UHR for psychosis with comorbid emotional symptoms. The assessment is performed at baseline, at the end of treatment, and at three-months’ follow-up, and includes: general psychopathology, anxiety and depression, positive and negative emotions, emotional dysregulation, personality, functionality, quality of life, cognitive distortions, insight and satisfaction with the UP intervention. 3 Discussion: This will be the first study of the efficacy, acceptability, and viability of the UP in a sample of young adults with UHR. The results of this study may have clinical implications, contributing to improving the model of care for young people who consult for underlying psychotic, anxiety, and/or depressive symptoms that can lead to high distress and dysfunctionality.